Light irradiation for treatment of acute carbon monoxide poisoning: an experimental study. Issue 1 (December 2016) - Tanaka, Taku; Kashimura, Takeshi; Ise, Marii; Lohman, Brandon; Taira, Yasuhiko
Abstract Background Because treatment modalities for carbon monoxide (CO) poisoning, especially normobaric oxygen and hyperbaric oxygen therapies, have limited effects and hyperbaric oxygen is not available at the scene where treatment is most needed, we conducted a study to determine and compare rates of carboxyhemoglobin (COHb) dissociation achieved in human in vitro blood samples under light radiation emitted at three levels of illuminance. This was done with a view toward eventual on-site application. Methods We drew blood from 10 volunteers, prepared 10 red blood cell solutions, and subjected each solution to a CO bubbling procedure to increase the COHb saturation. Samples of each bubbled solution were then divided between 3 beakers (beakers A, B, and C) for a total of 30 beakers. The solution in each beaker was exposed to a continuous flow of oxygen at 50 mL/min, and simultaneously for a period of 15 min, the beaker A and B solutions were irradiated with light emitted at 500, 000 and 100, 000 lux, respectively, from a halogen light source. The beaker C solutions were exposed to room light. At 3, 6, 9, 12, and 15 min, a 50-μL sample was pipetted from each of the 30 beakers for determination of its light absorbance and the COHb dissociation rate. Results Under each of the experimental conditions, dissociation progressed but at different rates, and starting at 3 min, the differences in rates between conditions were significant (P < 0.01). The dissociation rate was greatest with light emitted at 500, 000 lux. Conclusions Our results point toward the possibility of readily performed, acute photodissociation therapy for patients with CO poisoning.